A genome‐wide investigation of food addiction. Issue 6 (23rd April 2016) - Cornelis, Marilyn C.; Flint, Alan; Field, Alison E.; Kraft, Peter; Han, Jiali; Rimm, Eric B.; van Dam, Rob M.
Abstract : Objective: Evidence of parallels between drug addiction and eating behavior continues to accumulate. Genetic studies of addictive substances have yielded a number of susceptibility loci that point to common higher order genetic pathways underlying addiction. It was hypothesized that a genome‐wide association study (GWAS) of food addiction would yield significant enrichment in genes and pathways linked to addiction. Methods: A GWAS of food addiction, determined by the modified Yale Food Addiction Scale (mYFAS), was conducted among 9, 314 women of European ancestry, and results for enrichment of single‐nucleotide polymorphisms (SNPs) ( n = 44), genes ( n = 238), and pathways ( n = 11) implicated in drug addiction were examined. Results: Two loci met GW‐significance ( P < 2.5 × 10 −8 ) mapping to 17q21.31 and 11q13.4 that harbor genes with no obvious roles in eating behavior. GW results were significantly enriched for gene members of the MAPK signaling pathway ( P = 0.02). No candidate SNP or gene for drug addiction was significantly associated with food addiction after correction for multiple testing. Conclusions: In the first GWAS of mYFAS, suggestive loci worthy of further follow‐up were identified, but limited support was provided for shared genetic underpinnings of food addiction and drug addiction. The latter might be due to limited study power and knowledge of the genetics of drug addiction.